Effects of NaCl salinity on growth, morphology, photosynthesis and proline accumulation of Salvinia natans - Arunothai Jampeetong (2018)
The effects of NaCl salinity on growth, morphology and photosynthesis of Salvinia natans (L.) All. were investigated by growing plants in a growth chamber at NaCl concentrations of 0, 50, 100 and 150 mM. The relative growth rates were high (ca. 0.3 d-1) at salinities up to 50 mM and decreased to less than 0.2 d-1at higher salinities, but plants produced smaller and thicker leaves and had shorter stems and roots, probably imposed by the osmotic stress and lowered turgor pressure restricting cell expansion. Na+concentrations in the plant tissue only increased three-fold, but uptake of K+was reduced, resulting in very high Na+/K+ratios at high salinities, indicating that S. natans lacks mechanisms to maintain ionic homeostasis in the cells. The contents of proline in the plant tissue increased at high salinity, but concentrations were very low (<0.1 μmol g-1FW), indicating a limited capacity of S. natans to synthesize proline as a compatible compound. The potential photochemical efficiency of PSII (Fv/Fm) of S. natans remained unchanged at 50 mM NaCl but was reduced at higher salinities, and the photosynthetic capacity (ETRmax) was significantly reduced at 50 mM NaCl and higher. It is concluded that S. natans is a salt-sensitive species lacking physiological measures to cope with exposure to high NaCl salinity. At low salinities salts are taken up and accumulate in old leaves, and high growth rates are maintained because new leaves are produced at a higher rate than for plants not exposed to salt. © 2009 Elsevier B.V. All rights reserved.